The graphic design reader - Triggs, Teal; Atzmon, Leslie (Bloomsbury Visual Arts, 2019)
"The Graphic design reader features original visual essays which provide a critical platform for understanding and interpreting graphic design practice, as well as a wealth of illustrations accompanying key historical and contemporary texts from the 1920s to the present day." -- Provided by publisher.